Tuberculous otitis media: rare cause of recurrent facial nerve palsy - Tiwari, Vibhu; Singh, Rohit; Anand, V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Tuberculous otitis media (TOM) is a rare form of tuberculosis, due to tubercular otitis media, thick caseous material and granulation tissue gets deposited in middle ear cleft causing bone erosion, sequestration, ossicular destruction, heading loss which can be conductive or mixed and rarely facial paralysis. In this case report we discuss tubercular otitis media as a cause of recurrent facial nerve paralysis. 54 year old male patient with no known previous comorbidities presented to ENT OPD on 12 October 19 with complaints of scanty, mucopurulent foul smelling occasionally blood stained continuous otorrhoea (R)×02 years, painless progressive and persistent hearing loss ×1 year and recurrent (R) sided facial nerve palsy, 03 episodes in last 2 years which were spontaneous and sudden in onset, showed gradual recovery with oral medication. Tubercular otitis media is not a very common diagnosis with which an otolaryngologist comes across. It generally presents with otorrhea and hearing loss which mimics more commoner ear disease. Typical findings of multiple tympanic membrane perforations are not necessarily seen. There can be involvement of facial nerve and presence of refractory otorrhoea with atypical features may be considered indicative of tubercular pathology. A clinician should have high index of suspicion whenever there are signs which outlies symptoms in form of severity. This case highlights the diagnostic challenge and high index of clinical suspicion required for diagnosis. Combination of appropriate diagnostic modality along with good clinical vigilance will aid in early diagnosis and start of early medication which reduces chances of any subsequent complications.